2021
DOI: 10.3389/fnut.2021.705353
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Dietary Quality and Postpartum Depression in Lactating Women: A Cross-Sectional Survey in Urban China

Abstract: Background: Evidence on the effects of dietary quality on the risk of postpartum depression in the Chinese population is limited. This study aimed to examine the association between dietary quality and postpartum depression in Chinses lactating women.Methods: A total of 939 participants from 10 cities were included in this analysis. A one-time 24-h dietary recall was used to obtain the data on food consumption and dietary quality was assessed based on Diet Balance Index. The Edinburgh postnatal depression scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 62 publications
1
16
0
2
Order By: Relevance
“…Moreover, a statistically significant difference between the BMI categories among the five countries was found. Previous studies conducted in China (9) and Australia (3) showed a lower percentage (28.1%) of overweight postpartum women, where the mean postpartum BMI was 26.2 (5.0) which is similar to our participants' prepregnancy BMI. Regarding the other health characteristics, most of the postpartum women were not diagnosed with COVID-19, diabetes or gestational diabetes, hypertension, and thyroid disorders, despite that (75%) reported having health problems.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Moreover, a statistically significant difference between the BMI categories among the five countries was found. Previous studies conducted in China (9) and Australia (3) showed a lower percentage (28.1%) of overweight postpartum women, where the mean postpartum BMI was 26.2 (5.0) which is similar to our participants' prepregnancy BMI. Regarding the other health characteristics, most of the postpartum women were not diagnosed with COVID-19, diabetes or gestational diabetes, hypertension, and thyroid disorders, despite that (75%) reported having health problems.…”
Section: Discussionsupporting
confidence: 89%
“…Other than that, 64% of our participants were physically active and 77% did not smoke during pregnancy, which decreased the risk of chronic diseases as mentioned above. Around half of them reported suffering from mild depression and anxiety, which is higher than the proportion reported in the Urban China study (9). These results might be related to the lower intake of fish or omega-3 polyunsaturated fatty acids during pregnancy and the postpartum period, as reported by Hamazaki et al ( 21).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…For example, malnutrition was found to be an independent risk factor for depression in older outpatients in Turkey [ 32 ] and community-dwelling older individuals in Bangladesh [ 33 ] and China [ 34 ]. Poor dietary quality was significantly associated with postpartum depression in a sample of 939 Chinese lactating women [ 35 ]. An association between nutritional health risk and depression was also reported by previous studies involving Korean older adults with multiple chronic diseases [ 36 ] and community-dwelling Korean older adults [ 19 ].…”
Section: Discussionmentioning
confidence: 99%